Rekonstruksi Makna Kejujuran akademik Mahasiswa: Studi Penggunaan ChatGPT dalam Perspektif Etika Islam - Heni Ani Nuraeni; Irwan Baadilla; Ahmad Hidayatullah; Rokhmani Rokhmani; Siti Kodariah (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to analyze the level of ChatGPT usage, examine students’ perceptions of academic honesty in its use from an Islamic ethics perspective, and reconstruct the meaning of academic honesty in the era of Generative Artificial Intelligence (AI).Methods – This study used a sequential explanatory mixed-methods design. Quantitative data were gathered through questionnaires from 150 PBSI and PGSD students at Universitas Muhammadiyah Prof. DR. HAMKA, followed by in-depth interviews with 10 students. The qualitative data were analyzed using thematic analysis. Findings – The results indicate that the level of ChatGPT usage among students was high (80.0%). Students’ perceptions of academic honesty in using ChatGPT were also categorized as high (74.8%), with the highest scores found in the dimensions of amanah (trustworthiness) (84.8%) and academic responsibility (84.2%). In contrast, lower scores were observed in AI-use transparency (57.8%), originality of work (64.8%), and ?idq (truthfulness) (66.2%). Qualitative findings revealed a reconstruction of the meaning of academic honesty, shifting from honesty as complete independence toward honesty as responsible and transparent use of technology.Research Implications – This study was limited to students from two programs at one university. Its findings underscore the need to strengthen AI literacy, academic ethics, and institutional AI policies grounded in Islamic values: ?idq, amanah, mas’uliyyah, ihsan, and adab.